Analisis Manajemen Risiko Imbal Hasil Pada Perbankan Syariah Di Indonesia - Marpaung, Reza Rahmad (Maliki Interdisciplinary Journal, 2025)
The application of yield risk management in Islamic banking in Indonesia is an important element in maintaining the stability of bank performance while reflecting the principles of fairness and transparency in the Islamic financial system. Unlike conventional banking, which uses fixed interest rates, the Islamic system applies the principle of profit sharing, which contains elements of uncertainty and is greatly influenced by business performance. Therefore, Islamic banks must be able to effectively manage various inherent risks such as market risk, credit risk, liquidity risk, operational risk, and sharia risk. This study highlights the strategies implemented by Islamic banks in Indonesia such as Bank Syariah Indonesia (BSI) and BCA Syariah, ranging from strengthening internal systems, sharia supervision, utilizing digital technology, to customer education. Despite challenges such as the limited availability of sharia hedging instruments and low sharia financial literacy, this research indicates that with regulatory support, product innovation, and improved risk management, sharia banking in Indonesia has significant potential for sustainable growth and can make a positive contribution to the national economy.